Advertisements as shapers of social reality: a study of apple advertisements and their depiction of technology use for empowering people with special needs - Mokhtar, Aida (2018)
Disabled children in Malaysia should not be discriminated yet they encounter discriminatory treatment by being pitied, community and religious leaders believe that disabled children should be treated like normal, there was the issue of who is caring for them in future. For inclusion to happen, support needs to be provided to people with disabilities. The paper examines advertisements by Apple that showcase gadgets that provide support for the disabled using critical discourse analysis.